A PERSUASIVE APPROACH TO RESOLUTION OF BUSINESS DISPUTES CONTAINING CRIMINAL ELEMENTS FROM A JUSTICE PERSPECTIVE BASED ON PANCASILA - P. Siahaan, Herikson (Proceeding International Seminar of Islamic Studies, 2023)
Most business dispute resolution is carried out using litigation or dispute resolution through the trial process, which is the oldest method of dispute resolution in the world. Settlement of the dispute begins with filing a lawsuit with the district court and ends with a judge's decision. Dispute resolution through the judicial process can be referred to as law enforcement. In addition to dispute resolution through the litigation process, there is also dispute resolution through non-litigation, which is dispute resolution carried out using methods outside of court or using alternative dispute resolution institutions. In Indonesia, there are two types of non-litigation resolution, namely arbitration and alternative dispute resolution in accordance with Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution.